A low-halogen flame-retardant lithium battery aluminum-plastic film adhesive composition and preparation method thereof

By using modified epoxy resin, silane coupling agent and other raw materials in lithium battery aluminum-plastic film adhesives, a low-halogen flame retardant adhesive composition was developed, which solved the problem of traditional adhesives lacking flame retardant function, and achieved efficient flame retardant, heat resistance and bonding performance, ensuring the safety and environmental protection performance of lithium batteries.

CN119775935APending Publication Date: 2025-04-08BLUE OCEAN & BLACK STONE TECH CO LTD (FUJIAN)
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411951069.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-27
Publication Date
2025-04-08

AI Technical Summary

Technical Problem

Traditional lithium battery aluminum-plastic film adhesives lack flame retardant function or contain a large number of halogen compounds, which limits their application range and may cause environmental problems.

Method used

A low-halogen flame retardant lithium battery aluminum-plastic film adhesive composition is developed, using modified epoxy resin, silane coupling agent, polyurethane prepolymer, nanotitanium dioxide and modified hexaphenoxycyclotriphosphazene and other raw materials to improve flame retardant performance, heat resistance and bonding performance through synergistic action.

Benefits of technology

The adhesive composition has excellent flame retardant properties, heat resistance and bonding properties, ensuring that the lithium battery is safe and reliable under extreme conditions and has good environmental protection performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005214889470000081
    Figure BDA0005214889470000081
Patent Text Reader

Abstract

The present application relates to the technical field of aluminum-plastic film for lithium-ion batteries, and in particular to a low-halogen flame-retardant aluminum-plastic film adhesive composition for lithium-ion batteries and a preparation method thereof. A low-halogen flame-retardant aluminum-plastic film adhesive composition for lithium-ion batteries comprises the following raw materials: 45-60 parts of modified epoxy resin, 8-12 parts of silane coupling agent, 10-20 parts of polyurethane prepolymer, 8-12 parts of nano-titanium dioxide, 8-12 parts of flame retardant, and 1-3 parts of antioxidant, wherein the flame retardant is modified hexaphenoxy cyclotriphosphazene. The low-halogen flame-retardant aluminum-plastic film adhesive composition prepared in the present application has excellent flame retardant properties, heat resistance, bonding properties and mechanical properties, can maintain the safety and reliability of the battery under extreme conditions, and has good environmental performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of aluminum-plastic films for lithium-ion batteries, and in particular to a low-halogen flame-retardant lithium-ion battery aluminum-plastic film adhesive composition and a preparation method thereof. Background Art

[0002] In recent years, with the rapid growth of the new energy vehicle and portable electronic device markets, the demand for lithium batteries has increased significantly. As one of the important components of lithium batteries, aluminum-plastic film is widely used in the packaging of soft-pack lithium batteries due to its light weight, flexibility and good heat sealing performance. However, most of the adhesives used in traditional aluminum-plastic films do not have flame retardant functions, or the flame retardant components contain a large amount of halogen compounds, which not only limits its scope of application, but also may cause environmental problems. Therefore, the development of new low-halogen flame-retardant lithium battery aluminum-plastic film adhesives has become a research hotspot in the industry. Summary of the invention

[0003] In view of the shortcomings of the prior art, the present application provides a low-halogen flame retardant lithium battery aluminum-plastic film adhesive composition and a preparation method thereof. The low-halogen flame retardant lithium battery aluminum-plastic film adhesive composition prepared in the present application has excellent flame retardant properties, heat resistance and bonding properties, and can ensure the safety and reliability of the battery under extreme conditions.

[0004] In the first aspect, the present application provides a low-halogen flame-retardant lithium battery aluminum-plastic film adhesive composition, which adopts the following technical solution: A low-halogen flame-retardant lithium battery aluminum-plastic film adhesive composition comprises the following preparation raw materials, measured by weight: 45-60 parts of modified epoxy resin, 8-12 parts of silane coupling agent, 10-20 parts of polyurethane prepolymer, 8-12 parts of nano titanium dioxide, 8-12 parts of flame retardant, and 1-3 parts of antioxidant, wherein the flame retardant is modified hexaphenoxy cyclotriphosphazene.

[0005] By adopting the above technical scheme, modified epoxy resin: As one of the main components of the adhesive composition, the role of modified epoxy resin is mainly reflected in the following aspects: Increase flexibility: The modified epoxy resin contains polyurethane segments, which makes the composite adhesive have better flexibility and can adapt to complex shapes and surface conditions. Improve heat resistance: The modified epoxy resin has good heat resistance and can improve the stability of the composite adhesive in high temperature environments. Enhance bonding performance: The modified epoxy resin has strong bonding force and can significantly improve the bonding strength of the adhesive composition. Silane coupling agent can improve the dispersibility and compatibility of nano titanium dioxide. The role of polyurethane prepolymer is mainly reflected in the following aspects: The bonding performance of the adhesive composition is improved by copolymerizing polymer polyether polyols and dimer acid polyester polyols with side groups. By adding phosphorus-containing polyols to the polyurethane prepolymer, the polyurethane prepolymer has flame retardant function. Nano titanium dioxide improves mechanical properties. Flame retardant: Modified hexaphenoxy cyclotriphosphazene as a flame retardant has excellent flame retardant properties and high thermal stability, and has the characteristics of water resistance, oxidation resistance and low smoke production during combustion. The main function of the antioxidant is to improve the antioxidant properties of the material and extend the service life of the material. In summary, each component plays its own role in the adhesive composition, and at the same time, through synergistic effects, the flame retardant properties, heat resistance and bonding properties of the adhesive composition are jointly improved to ensure the safety and reliability of the battery under extreme conditions.

[0006] Preferably, the modified epoxy resin comprises the following raw materials in parts by mass: 5-30 parts of bisphenol A epoxy resin E-442, 20-30 parts of hexamethylene diisocyanate, 0.05-0.1 parts of monobutyl tin triisooctanoate, 5-8 parts of n-dodecyl alcohol, and 20-30 parts of polypropylene glycol diglycidyl ether.

[0007] Preferably, the preparation method of the modified epoxy resin is as follows: according to the mass fractions, bisphenol A epoxy resin E-44 and monobutyl tin triisooctanoate are added to a reaction kettle, vacuum dehydration is carried out for 2-3 hours, hexamethylene diisocyanate is added, and the reaction is carried out at 80° C. for 3-4 hours; when the residual NCO is close to 0, polypropylene glycol diglycidyl ether and n-dodecyl alcohol are added in a formula ratio, the reaction is continued for 3-4 hours, the temperature is reduced to below 30° C., and the material is discharged to obtain the modified epoxy resin.

[0008] By adopting the above technical scheme, the modified epoxy resin is obtained by reacting bisphenol A epoxy resin E-44 with other raw materials. Among them, bisphenol A epoxy resin E-44 has good strength and adhesion. At the same time, by adding raw materials such as hexamethylene diisocyanate and polypropylene glycol diglycidyl ether, the modified epoxy resin has better flexibility and heat resistance. Secondly, the role of the modified epoxy resin in the adhesive composition is mainly reflected in the following aspects: 1. Increase flexibility: The modified epoxy resin contains polyurethane segments, which makes the composite adhesive have better flexibility and can adapt to complex shapes and surface conditions. 2. Improve heat resistance: The modified epoxy resin has good heat resistance and can improve the stability of the composite adhesive in high temperature environment. 3. Enhance bonding performance: The modified epoxy resin has strong bonding force and can significantly improve the bonding strength of the adhesive composition.

[0009] Preferably, the silane coupling agent is composed of a modified silane coupling agent and γ-glycidyloxypropyltrimethoxysilane in a mass ratio of 3:2-3.

[0010] By adopting the above technical scheme, the silane coupling agent can effectively improve the bonding force between the adhesive and the substrate through its unique chemical structure. At the same time, the functional groups in the silane coupling agent can react with the active groups in the modified epoxy resin and the polyurethane prepolymer to form a stable chemical bond, thereby improving the bonding strength of the adhesive. The silane coupling agent can improve the dispersibility of nano-titanium dioxide and make it evenly distributed in the adhesive, thereby improving the overall performance of the adhesive. At the same time, the silane coupling agent can also improve the compatibility between nano-titanium dioxide and the adhesive, reduce interface defects, and improve the heat resistance and flame retardancy of the adhesive. Synergistic effect between modified silane coupling agent and γ-glycidyloxypropyltrimethoxysilane: The modified silane coupling agent and γ-glycidyloxypropyltrimethoxysilane are composed of a mass fraction ratio of 3:2-3, which can ensure the synergistic effect between the two substances is maximized. The modified silane coupling agent provides enhanced chemical bonding and adhesion, while γ-glycidyloxypropyltrimethoxysilane provides additional chemically active groups, which further improves the adhesive's bonding and heat resistance. This synergistic effect not only improves the adhesive's bonding and heat resistance, but also improves the adhesive's flame retardant properties through the combined action of the modified silane coupling agent and γ-glycidyloxypropyltrimethoxysilane. This is crucial for the safety and reliability of lithium batteries. In summary, the silane coupling agent and its synergistic effect with the modified silane coupling agent and γ-glycidyloxypropyltrimethoxysilane play a key role in improving the flame retardant, heat resistance and bonding properties of the lithium battery aluminum-plastic film adhesive composition. The preparation of this composite material not only meets the safety and reliability requirements of lithium batteries under extreme conditions, but also provides new possibilities for improving the performance of lithium batteries.

[0011] Preferably, the preparation method of the modified silane coupling agent comprises the following steps: S51, dissolving γ-isocyanatepropyltrimethoxysilane and vinyl alcohol in cyclohexane, adding tetrabutyl titanate, stirring and reacting at a temperature of 70-80° C. for 4-6 hours, and then continuing the reaction at a vacuum degree of 10 Pa for 1-2 hours to obtain olefin-containing siloxane; S52. In cyclohexane, olefin-containing siloxane, isobutyraldehyde and a catalyst are reacted at a temperature of 30-40° C. and with oxygen introduced for 2-3 hours to obtain the modified silane coupling agent.

[0012] By adopting the above technical scheme, γ-isocyanate propyl trimethoxysilane and vinyl alcohol are reacted to obtain olefin-containing siloxane, and the olefin-containing siloxane is then subjected to epoxidation reaction to obtain a modified silane coupling agent containing a variety of different functional groups. The modified silane coupling agent containing a variety of different functional groups is then used to prepare an adhesive composition. Due to the good synergistic effect between different active groups, the obtained adhesive composition has excellent flame retardant properties, heat resistance and bonding properties, and can ensure the safety and reliability of the battery under extreme conditions.

[0013] Preferably, the reaction molar ratio of the γ-isocyanate propyltrimethoxysilane to vinyl alcohol is 1:1-2.

[0014] Preferably, the preparation method of the polyurethane prepolymer is as follows: according to the mass fractions, 15-20 parts of polyether polyol, 15-20 parts of dimer acid polyester polyol with side groups and 45-55 parts of diphenylmethane diisocyanate are reacted at 80-85°C for 2-2.5h, and then 10 parts of phosphorus-containing polyol are added and the reaction is continued at 80-85°C for 1.5-2h, and the NCO content at the reaction end point is strictly controlled to be 10-20%, so as to obtain the polyurethane prepolymer.

[0015] By adopting the above technical scheme, the molecular structure of the polyurethane prepolymer prepared is precisely designed. The bonding performance of the adhesive composition is improved by copolymerizing the high molecular weight polyether polyol and the dimer acid polyester polyol with a side group. The mechanical properties of the adhesive composition can be significantly improved when combined with a modified epoxy resin. At the same time, by adding phosphorus-containing polyols to the polyurethane prepolymer, the polyurethane prepolymer has a flame retardant function.

[0016] Preferably, the preparation method of the modified hexaphenoxy cyclotriphosphazene comprises the following steps: S81. According to the mass fractions, 693 parts of hexaphenoxy cyclotriphosphazene and 124 parts of γ-(methacryloyloxy)propyltrimethoxysilane are added to 1200 parts of acetone, and the mixture is heated to 75-80°C under nitrogen protection, and kept warm for 1-1.3 hours. Then, 0.8 parts of azobisisoheptanenitrile are dissolved in 20 parts of acetone to obtain an azobisisoheptanenitrile solution, and the azobisisoheptanenitrile solution is slowly added dropwise within 1 hour. After reacting for 10-12 hours, the acetone is removed by rotary evaporation to obtain γ-(methacryloyloxy)propyltrimethoxysilane-modified hexaphenoxy cyclotriphosphazene; S82. Dry nano-silica with a particle size of 20-30 nm at 100-120°C for 6-8h according to the mass fraction, then add 50 parts of the dried nano-silica and 150 parts of γ-(methacryloyloxy)propyltrimethoxysilane-modified hexaphenoxycyclotriphosphazene to 1500 parts of anhydrous ethanol, stir evenly, and reflux at 78-82°C for 16-20h under nitrogen protection. After the reaction is completed, filter, wash with ethanol, and dry to obtain modified hexaphenoxycyclotriphosphazene.

[0017] By adopting the above technical scheme, hexaphenoxy cyclotriphosphazene belongs to phosphorus-nitrogen flame retardant, which has a unique PN hybrid structure, giving it excellent flame retardant performance and high thermal stability, and has the characteristics of water resistance, oxidation resistance and low smoke generation during combustion, and hexaphenoxy cyclotriphosphazene can be chemically grafted to the surface of nano-silica particles after being modified by silane coupling agent to prepare a new type of phosphorus-nitrogen nano flame retardant, and applied to the adhesive composition. Since the silica nanoparticles can significantly improve the combustion performance of the adhesive such as the heat release rate, the organic phosphorus-nitrogen and the nanoparticles have obvious synergistic flame retardant effect. It can significantly improve the mechanical properties, heat resistance and flame retardant properties of the adhesive composition.

[0018] Preferably, the antioxidant is bis(2,4-dicumylphenyl)pentaerythritol diphosphite.

[0019] In a second aspect, the present application provides a method for preparing a low-halogen flame-retardant lithium battery aluminum-plastic film adhesive composition, using the following technical solution: As a general technical concept, the present application also provides a method for preparing the above-mentioned low-halogen flame-retardant lithium battery aluminum-plastic film adhesive composition, comprising the following steps: According to the mass proportions, the modified epoxy resin is heated and melted, and the silane coupling agent is added and stirred thoroughly and evenly, and then the polyurethane prepolymer, nano titanium dioxide, flame retardant and antioxidant are added in sequence and stirred continuously until they are completely dispersed to obtain a low-halogen flame-retardant lithium battery aluminum-plastic film adhesive composition.

[0020] In summary, the present application includes at least one of the following beneficial technical effects: 1. Excellent flame retardant performance: Due to the use of modified hexaphenoxy cyclotriphosphazene as a flame retardant, the adhesive composition has significant flame retardant performance. At the same time, the hexaphenoxy cyclotriphosphazene modified by the silane coupling agent can be chemically grafted to the surface of nano-silica particles to form a phosphorus-nitrogen nano flame retardant, which further improves the flame retardant effect.

[0021] 2. Good heat resistance: The use of modified epoxy resin and polyurethane prepolymer improves the heat resistance of the adhesive composition, enabling it to remain stable in high temperature environments.

[0022] 3. Enhanced bonding performance: The modified epoxy resin and polyurethane prepolymer have strong bonding strength, which can significantly improve the bonding strength of the adhesive composition. At the same time, the bonding performance of the adhesive composition is further improved through the copolymerization of the precisely designed polyurethane prepolymer molecular structure and the high molecular weight polyether polyol and the dimer acid polyester polyol with side groups.

[0023] 4. Excellent mechanical properties: The combination of modified epoxy resin, nano-titanium dioxide and polyurethane prepolymer significantly improves the mechanical properties of the adhesive composition.

[0024] 5. Improved safety and reliability: This adhesive composition can maintain excellent flame retardancy, heat resistance and bonding properties under extreme conditions, thereby ensuring the safety and reliability of lithium batteries.

[0025] 6. Environmental performance: Due to the use of environmentally friendly materials such as low-halogen flame retardants and modified epoxy resins, this adhesive composition has good environmental performance. DETAILED DESCRIPTION

[0026] The implementation scheme of the present application will be described in detail below in conjunction with the examples, but those skilled in the art will understand that the following examples are only used to illustrate the present application and should not be considered to limit the scope of the present application. If the specific conditions are not specified in the examples, they are carried out according to conventional conditions or conditions recommended by the manufacturer. The reagents or instruments used without indicating the manufacturer are all conventional products that can be purchased commercially. The polyether polyols were purchased from Shandong Bluestar Dongda Chemical Co., Ltd., model DL-4000D; the dimer acid polyester polyols with side groups were purchased from Shanghai Jingri New Materials Technology Co., Ltd., model DA-21; the phosphorus-containing polyols were purchased from Clariant, Germany, model Exolit OP550.

[0027] In the following examples and preparation examples, 1 part means 100 g.

[0028] Preparation Example 1 Preparation of modified epoxy resin A modified epoxy resin comprises the following raw materials in parts by weight: 28 parts of bisphenol A epoxy resin E-44, 28 parts of hexamethylene diisocyanate, 0.07 parts of monobutyl tin triisooctanoate, 6 parts of n-dodecyl alcohol, and 24 parts of polypropylene glycol diglycidyl ether. The preparation method of the modified epoxy resin is as follows: according to the parts by weight, bisphenol A epoxy resin E-44 and monobutyl tin triisooctanoate are added into a reaction kettle, vacuum dehydration is performed for 2.3 hours, hexamethylene diisocyanate is added, and the reaction is carried out at 80° C. for 3.4 hours; when the residual NCO is close to 0, polypropylene glycol diglycidyl ether and n-dodecyl alcohol in a formula ratio are added, the reaction is continued for 4 hours, the temperature is lowered to below 30° C., and the material is discharged to obtain the modified epoxy resin.

[0029] Preparation Example 2 Preparation of modified silane coupling agent The preparation method of the modified silane coupling agent comprises the following steps: S51, dissolving 1 mol of γ-isocyanatepropyltrimethoxysilane and 2 mol of vinyl alcohol in 4 mol of cyclohexane, adding 0.005 mol of tetrabutyl titanate, stirring and reacting at a temperature of 78° C. for 5 h, and then continuing the reaction at a vacuum degree of 10 Pa for 1.5 h, finally removing low-boiling substances by reduced pressure distillation, and performing column chromatography to obtain olefin-containing siloxane; S52, siloxane containing olefins reacts under the conditions of activated carbon-supported palladium nanoparticles as a catalyst, oxygen as an oxygen source, and isobutylaldehyde as a sacrificial agent to generate a modified silane coupling agent with an epoxy group, with a yield of 85%. Specific reaction: 150mL of dichloromethane, 50mmol of siloxane containing olefins, 200mmol of isobutylaldehyde and 1g of catalyst are stirred and mixed at 30°C for 4h, and oxygen (content ≥99.99%) is kept flowing during the stirring process. The final reaction mixture is removed by removing the catalyst and then distilling under reduced pressure to remove low-boiling substances, and the modified silane coupling agent is obtained.

[0030] Preparation Example 3 Preparation of polyurethane prepolymer The preparation method of the polyurethane prepolymer is as follows: according to the mass fractions, 19 parts of polyether polyol, 19 parts of dimer acid polyester polyol with side groups and 52 parts of diphenylmethane diisocyanate are reacted at 83° C. for 2.3 hours, and then 10 parts of phosphorus-containing polyol are added and the reaction is continued at 85° C. for 2 hours, and the NCO content at the reaction end point is strictly controlled to be 15% to obtain the polyurethane prepolymer.

[0031] Preparation Example 4 Preparation of modified hexaphenoxy cyclotriphosphazene The preparation method of modified hexaphenoxy cyclotriphosphazene comprises the following steps: S81. According to the mass fractions, 693 parts of hexaphenoxy cyclotriphosphazene and 124 parts of γ-(methacryloyloxy)propyltrimethoxysilane are added to 1200 parts of acetone, and the temperature is raised to 80° C. under nitrogen protection, and the temperature is kept for 1 hour. Then, 0.8 parts of azobisisoheptanenitrile are dissolved in 20 parts of acetone to obtain an azobisisoheptanenitrile solution, and the azobisisoheptanenitrile solution is slowly added dropwise within 1 hour. After reacting for 10 hours, the acetone is removed by rotary evaporation to obtain γ-(methacryloyloxy)propyltrimethoxysilane-modified hexaphenoxy cyclotriphosphazene; S82. Dry nano-silica with an average particle size of 30 nanometers at 120°C for 6 hours according to the mass fractions, then add 50 parts of the dried nano-silica and 150 parts of γ-(methacryloyloxy)propyltrimethoxysilane-modified hexaphenoxycyclotriphosphazene to 1500 parts of anhydrous ethanol, stir evenly, and reflux at 78°C for 120 hours under nitrogen protection. After the reaction is completed, filter, wash with ethanol, and dry to obtain modified hexaphenoxycyclotriphosphazene.

[0032] Example 1 A low-halogen flame-retardant lithium battery aluminum-plastic film adhesive composition comprises the following raw materials, measured by weight: 45 parts of modified epoxy resin, 8 parts of silane coupling agent, 10 parts of polyurethane prepolymer, 8 parts of nano titanium dioxide (average particle size 20 nanometers), 8 parts of modified hexaphenoxy cyclotriphosphazene, and 1 part of bis(2,4-dicumylphenyl)pentaerythritol diphosphite. The silane coupling agent is composed of a modified silane coupling agent and γ-glycidyloxypropyltrimethoxysilane in a weight ratio of 3:2.

[0033] The method for preparing the low-halogen flame-retardant lithium battery aluminum-plastic film adhesive composition comprises the following steps: According to the mass fractions, the modified epoxy resin is heated and melted, and the silane coupling agent is added and stirred thoroughly and evenly, and then the polyurethane prepolymer, nano titanium dioxide, modified hexaphenoxy cyclotriphosphazene and bis(2,4-dicumylphenyl)pentaerythritol diphosphite are added in sequence and stirred continuously until they are completely dispersed to obtain a low-halogen flame-retardant lithium battery aluminum-plastic film adhesive composition.

[0034] Example 2 A low-halogen flame-retardant lithium battery aluminum-plastic film adhesive composition comprises the following raw materials, measured by weight: 60 parts of modified epoxy resin, 12 parts of silane coupling agent, 20 parts of polyurethane prepolymer, 12 parts of nano titanium dioxide (average particle size of 20 nanometers), 12 parts of modified hexaphenoxy cyclotriphosphazene, and 3 parts of bis(2,4-dicumylphenyl)pentaerythritol diphosphite. The silane coupling agent is composed of a modified silane coupling agent and γ-glycidyloxypropyltrimethoxysilane in a weight ratio of 3:3.

[0035] The method for preparing the low-halogen flame-retardant lithium battery aluminum-plastic film adhesive composition comprises the following steps: According to the mass fractions, the modified epoxy resin is heated and melted, and the silane coupling agent is added and stirred thoroughly and evenly, and then the polyurethane prepolymer, nano titanium dioxide, modified hexaphenoxy cyclotriphosphazene and bis(2,4-dicumylphenyl)pentaerythritol diphosphite are added in sequence and stirred continuously until they are completely dispersed to obtain a low-halogen flame-retardant lithium battery aluminum-plastic film adhesive composition.

[0036] Example 3 A low-halogen flame-retardant lithium battery aluminum-plastic film adhesive composition comprises the following raw materials, measured by weight: 53 parts of modified epoxy resin, 10 parts of silane coupling agent, 15 parts of polyurethane prepolymer, 10 parts of nano titanium dioxide (average particle size of 20 nanometers), 10 parts of modified hexaphenoxy cyclotriphosphazene, and 2 parts of bis(2,4-dicumylphenyl)pentaerythritol diphosphite; the silane coupling agent is composed of a modified silane coupling agent and γ-glycidyloxypropyltrimethoxysilane in a weight ratio of 3:2.5.

[0037] The method for preparing the low-halogen flame-retardant lithium battery aluminum-plastic film adhesive composition comprises the following steps: According to the mass fractions, the modified epoxy resin is heated and melted, and the silane coupling agent is added and stirred thoroughly and evenly, and then the polyurethane prepolymer, nano titanium dioxide, modified hexaphenoxy cyclotriphosphazene and bis(2,4-dicumylphenyl)pentaerythritol diphosphite are added in sequence and stirred continuously until they are completely dispersed to obtain a low-halogen flame-retardant lithium battery aluminum-plastic film adhesive composition.

[0038] Comparative Example 1 The same as Example 3, except that: 68 parts of modified epoxy resin and 0 parts of polyurethane prepolymer.

[0039] Comparative Example 2 The same as Example 3, except that: 20 parts of nano titanium dioxide (average particle size 20 nanometers) and 0 parts of modified hexaphenoxy cyclotriphosphazene.

[0040] Comparative Example 3 The same as Example 3, except that: the silane coupling agent is a modified silane coupling agent.

[0041] Comparative Example 4 The same as Example 3, except that: the silane coupling agent is γ-glycidyloxypropyltrimethoxysilane.

[0042] Comparative Example 5 The same as Example 3, except that an equal amount of bisphenol A epoxy resin E-44 is used instead of the modified epoxy resin.

[0043] Performance testing The low-halogen flame-retardant lithium battery aluminum-plastic film adhesive compositions prepared in Examples 1 to 3 and Comparative Examples 1 to 5 were sampled and subjected to the following tests. The results are shown in Table 1.

[0044] The adhesive composition was poured onto a 100 mm×100 mm×5 mm polytetrafluoroethylene plate to form a film by natural casting, dried at room temperature for 12 hours, and then placed in an oven at 135° C. to dry for 24 hours to obtain an adhesive film.

[0045] Refer to GB / T531.1-2008 and use Shore A hardness tester to test the film hardness.

[0046] With reference to GB / T1040.3-2006, a universal tensile testing machine was used to test the mechanical properties of the film at a test rate of 50 mm / min.

[0047] The adhesive was coated on a 20cm×8cm aluminum-plastic film with a coating thickness of 30μm, dried naturally, and hot pressed at 160°C. The peel strength was tested using an electronic universal testing machine with a tensile rate of 300mm / min.

[0048] Peel strength (according to the provisions of B / T 8808-1988 "Peel test method for soft composite plastic materials").

[0049] High temperature peeling test: refer to the peeling strength test method and test the specimen at 120℃.

[0050] Refer to GB / T2406.2-2009 and use the limiting oxygen index tester to test the limiting oxygen index of the material.

[0051] Table 1 Performance test Analyzing the data in Table 1, we can see that: 1) The low-halogen flame-retardant lithium battery aluminum-plastic film adhesive composition prepared in Examples 1 to 3 has excellent flame retardancy, heat resistance and bonding properties, and can ensure the safety and reliability of the battery under extreme conditions.

[0052] 2) The performance comparison analysis of the low-halogen flame-retardant lithium battery aluminum-plastic film adhesive composition prepared in Example 3 and Comparative Example 1 shows that the addition of the polyurethane prepolymer prepared in the present application, whose molecular structure has been precisely designed, improves the bonding performance of the adhesive composition through copolymerization of high molecular weight polyether polyol and dimer acid polyester polyol with side groups, and can significantly improve the mechanical properties of the adhesive composition when combined with modified epoxy resin; at the same time, by adding phosphorus-containing polyol to the polyurethane prepolymer, the polyurethane prepolymer has a flame retardant function.

[0053] 3) The performance comparison analysis of the low-halogen flame-retardant lithium battery aluminum-plastic film adhesive composition prepared in Example 3 and Comparative Example 2 shows that hexaphenoxy cyclotriphosphazene belongs to a phosphorus-nitrogen type flame retardant, which has a unique PN hybrid structure, giving it excellent flame retardant properties and high thermal stability, and has the characteristics of water resistance, oxidation resistance and low smoke generation during combustion. In addition, hexaphenoxy cyclotriphosphazene can be chemically grafted to the surface of nano-silica particles after modification by a silane coupling agent to prepare a new type of phosphorus-nitrogen nano flame retardant, and applied to the adhesive composition. Since the silica nanoparticles can significantly improve the combustion properties of the adhesive such as the heat release rate, the organic phosphorus-nitrogen and the nanoparticles have a significant synergistic flame retardant effect. It can significantly improve the mechanical properties, heat resistance and flame retardant properties of the adhesive composition.

[0054] 4) The performance comparison analysis of the low-halogen flame-retardant lithium battery aluminum-plastic film adhesive composition prepared in Example 3 and Comparative Examples 3-4 shows that the silane coupling agent is composed of a modified silane coupling agent and γ-glycidyloxypropyltrimethoxysilane in a mass ratio of 3:2.5, and the silane coupling agent can effectively improve the bonding force between the adhesive and the substrate through its unique chemical structure. The flame retardant performance, heat resistance and bonding performance of the lithium battery aluminum-plastic film adhesive composition are improved by the combined effect between the modified silane coupling agent and γ-glycidyloxypropyltrimethoxysilane.

[0055] 5) The performance comparison analysis of the low-halogen flame-retardant lithium battery aluminum-plastic film adhesive composition obtained in Example 3 and Comparative Example 5 shows that the modified epoxy resin prepared in the present application is obtained by reacting bisphenol A epoxy resin E-44 with other raw materials. At the same time, by adding raw materials such as hexamethylene diisocyanate and polypropylene glycol diglycidyl ether, the modified epoxy resin has better flexibility and heat resistance. The modified epoxy resin contains polyurethane segments, which makes the composite adhesive have better flexibility and can adapt to complex shapes and surface conditions. The modified epoxy resin has good heat resistance and can improve the stability of the composite adhesive in high temperature environments. The modified epoxy resin has strong adhesion and can significantly improve the bonding strength of the adhesive composition.

[0056] The above embodiments are only used to explain the technical solutions of the present application rather than to limit them. Although the above embodiments provide a specific description of the present application, relevant technical personnel should understand that the specific implementation methods of the present application can still be modified or replaced by equivalents, and any modifications and equivalent replacements that do not depart from the spirit and scope of the present application should be included in the protection scope of the present application.

Claims

1. A low-halogen flame-retardant lithium battery aluminum-plastic film adhesive composition, characterized in that: The preparation raw materials include the following by weight: 45-60 parts of modified epoxy resin, 8-12 parts of silane coupling agent, 10-20 parts of polyurethane prepolymer, 8-12 parts of nano titanium dioxide, 8-12 parts of flame retardant and 1-3 parts of antioxidant, wherein the flame retardant is modified hexaphenoxy cyclotriphosphazene.

2. A low-halogen flame-retardant lithium battery aluminum-plastic film adhesive composition according to claim 1, characterized in that: The modified epoxy resin comprises the following raw materials in parts by weight: 25-30 parts of bisphenol A epoxy resin E-44, 20-30 parts of hexamethylene diisocyanate, 0.05-0.1 parts of monobutyl tin triisooctanoate, 5-8 parts of n-dodecyl alcohol, and 20-30 parts of polypropylene glycol diglycidyl ether.

3. A low-halogen flame-retardant lithium battery aluminum-plastic film adhesive composition according to claim 2, characterized in that: The preparation method of the modified epoxy resin is as follows: according to the mass fractions, bisphenol A epoxy resin E-44 and monobutyl tin triisooctanoate are added into a reaction kettle, vacuum dehydration is performed for 2-3 hours, hexamethylene diisocyanate is added, and the reaction is performed at 80° C. for 3-4 hours; when the residual NCO is close to 0, polypropylene glycol diglycidyl ether and n-dodecyl alcohol in a formula ratio are added, the reaction is continued for 3-4 hours, the temperature is lowered to below 30° C., and the material is discharged to obtain the modified epoxy resin.

4. A low-halogen flame-retardant lithium battery aluminum-plastic film adhesive composition according to claim 1, characterized in that: The silane coupling agent is composed of a modified silane coupling agent and gamma-glycidyloxypropyltrimethoxysilane in a mass ratio of 3:2-3.

5. A low-halogen flame-retardant lithium battery aluminum-plastic film adhesive composition according to claim 4, characterized in that: The preparation method of the modified silane coupling agent comprises the following steps: S51, dissolving γ-isocyanatepropyltrimethoxysilane and vinyl alcohol in cyclohexane, adding tetrabutyl titanate, stirring and reacting at a temperature of 70-80° C. for 4-6 hours, and then continuing the reaction at a vacuum degree of 10 Pa for 1-2 hours to obtain olefin-containing siloxane; S52. In cyclohexane, olefin-containing siloxane, isobutyraldehyde and a catalyst are reacted at a temperature of 30-40° C. and with oxygen introduced for 2-3 hours to obtain the modified silane coupling agent.

6. A low-halogen flame-retardant lithium battery aluminum-plastic film adhesive composition according to claim 4, characterized in that: The reaction molar ratio of the γ-isocyanate propyltrimethoxysilane and vinyl alcohol is 1:1-2.

7. A low-halogen flame-retardant lithium battery aluminum-plastic film adhesive composition according to claim 1, characterized in that: The preparation method of the polyurethane prepolymer is as follows: according to the mass fractions, 15-20 parts of polyether polyol, 15-20 parts of dimer acid polyester polyol with side groups and 45-55 parts of diphenylmethane diisocyanate are reacted at 80-85° C. for 2-2.5 hours, and then 10 parts of phosphorus-containing polyol are added and the reaction is continued at 80-85° C. for 1.5-2 hours, and the NCO content at the reaction end point is strictly controlled to be 10-20%, so as to obtain the polyurethane prepolymer.

8. The low-halogen flame-retardant lithium battery aluminum-plastic film adhesive composition according to claim 1, characterized in that: The preparation method of the modified hexaphenoxy cyclotriphosphazene comprises the following steps: S81. According to the mass fractions, 693 parts of hexaphenoxy cyclotriphosphazene and 124 parts of γ-(methacryloyloxy)propyltrimethoxysilane are added to 1200 parts of acetone, and the mixture is heated to 75-80°C under nitrogen protection, and kept warm for 1-1.3 hours. Then, 0.8 parts of azobisisoheptanenitrile are dissolved in 20 parts of acetone to obtain an azobisisoheptanenitrile solution. The azobisisoheptanenitrile solution is slowly added dropwise within 1 hour, and then the mixture is reacted for 10-12 hours, and the acetone is removed by rotary evaporation to obtain γ-(methacryloyloxy)propyltrimethoxysilane-modified hexaphenoxy cyclotriphosphazene. S82. Dry nano-silica with a particle size of 20-30 nanometers at 100-120°C for 6-8 hours according to the mass fraction, then add 50 parts of the dried nano-silica and 150 parts of γ-(methacryloyloxy)propyltrimethoxysilane-modified hexaphenoxycyclotriphosphazene to 1500 parts of anhydrous ethanol, stir evenly, and reflux at 78-82°C for 16-20 hours under nitrogen protection. After the reaction is completed, filter, wash with ethanol, and dry to obtain modified hexaphenoxycyclotriphosphazene.

9. The low-halogen flame-retardant lithium battery aluminum-plastic film adhesive composition according to claim 1, characterized in that: The antioxidant is bis(2,4-dicumylphenyl)pentaerythritol diphosphite.

10. A method for preparing a low-halogen flame-retardant lithium battery aluminum-plastic film adhesive composition as claimed in any one of claims 1 to 9, characterized in that: The following steps are involved: According to the mass proportions, the modified epoxy resin is heated and melted, and the silane coupling agent is added and stirred thoroughly and evenly, and then the polyurethane prepolymer, nano titanium dioxide, flame retardant and antioxidant are added in sequence and stirred continuously until they are completely dispersed to obtain a low-halogen flame-retardant lithium battery aluminum-plastic film adhesive composition.

Citation Information

Cited By

  • High-flame-retardant polyurethane insulation board and preparation method thereof

    CN121406122A